Profiling Pigmented Plants Cell Membrane Permeability on Different Solvents Condition - Afif Eka Rahma Setiyanto; Aisyah Fajriati; Nifda Nurika; Shofiyyah Adiibah Lillah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2023)
This study aims to observe the effect of temperature treatment and organic solvents on the permeability of the cell membrane. Carrot, potato, and purple sweet potato specimens were soaked in different organic solvents, namely 35% alcohol, 70% alcohol, cold water, and room temperature water. The research method used is descriptive qualitative. Data collection is done by experiment and documentation. The dependent variable of this research is the final concentration of the organic solvent and the first time the organic solvent changes color (release time). The results show that each specimen has different results. Carrots produce a low concentration of alcohol with a release time of 20-35 minutes and do not change the color of the water. Turmeric and purple sweet potato produce a higher concentration of alcohol than water. Turmeric and purple yam release time on alcohol is 5 minutes and is faster than the release time of turmeric and purple yam on water. The best solvent for the three specimens is 70% alcohol because it produces the highest concentration and the fastest release time.